"Vanishing" pulmonary valve stenosis - Nofil I Arain; James H Moller; Lee A Pyles; Shanthi Sivanandam (Wolters Kluwer Medknow Publications, 2012)
Objective: Both spontaneous resolution and progression of mild pulmonary valve stenosis (PS) have been reported. We reviewed characteristics of the pulmonary valve (PV) to determine factors that could influence resolution of mild PS. Methods: Fifteen asymptomatic pediatric patients with spontaneous resolution of isolated mild PS were retrospectively reviewed. Results: There was no correlation between the PV gradient, clinical presentation, age at diagnosis, or PV morphology. The PV annulus was small at initial presentation, which normalized at follow up. When corrected for the body surface area (z-score), the PV annulus was normal in all patients, including at initial evaluation. Conclusions: Based on our observation, neither age at diagnosis, nor PV-morphology-influenced resolution of mild PS. The variable clinical presentation makes it difficult to categorize and observe mild PS by auscultation alone. The PV annulus z-score could be a useful adjunct to determine the course and serial observation of mild PS.